Understanding doctor beauty influencers how source credibilty influcences skincare purchase intention - Alya Alfina; Rosa Prafitri Juniarti (Jurnal Ilmu Manajemen, 2026)
The proliferation of beauty influencers' skincare information is frequently inauthentic and inaccurate, leading audiences to scrutinise the credibility of online content more than ever before. This study examines the impact of the trustworthiness of beauty influencer doctors on TikTok on skincare purchase intentions, both directly and via parasocial interactions. This research employed quantitative methodologies, administering surveys to 238 participants and utilising SEM PLS data analysis techniques. Overall, the variables of attractiveness, expertise, trustworthiness, and parasocial interactions are proven to contribute to shaping the audience's purchase intention towards skincare products. However, there are differences in contribution. The findings indicated that trust positively affected purchasing intentions both directly and via parasocial interactions. Attractiveness necessitated mediation, while skill exerted a direct influence. These findings indicate that purchasing intentions are established rationally and that views regarding attitudes and normative beliefs are rational. Consequently, skincare marketers must identify which physicians, as beauty influencers, exhibit substantial trustworthiness and strong parasocial interactions to stimulate purchase intentions for skincare products.